The right to organise: critiquing the role of trade unions in shaping work relations in post-apartheid South Africa - Nyathi, Mthokozisi (Rhodes University, Faculty of Law, Law, 2011)
Organised labour continues to play a prominent role in shaping employment relations in South Africa. The individual worker is powerless and in a weaker bargaining position against his employer. The advent of democracy was accompanied by numerous interventions to level the historically uneven bargaining field. The trade union movement has made and consolidated significant gains since the advent of democracy. It however faces a plethora of new challenges, such as the negative forces of globalisation, declining membership (often associated with high levels of unemployment and the changing nature of work from standard to atypical employment), the resurfacing of adversarialism in the bargaining process, and numerous shortcomings inherent in forums established to facilitate corporatism. Business is intensifying its calls for investor-friendly policies, which effectively mean a relaxation of labour policies. The trade union movement faces an enormous task of rebuilding confidence and credibility among its members and at the same time showing some commitment to other social actors, government and business, that it is committed to contribute to economic growth and employment creation. The central focus of this thesis will be to highlight the gains made by the trade union movement, the numerous challenges threatening their existence, and how they have attempted to redefine their role in the face of these challenges. It will attempt to offer advice on how trade unions can continue to play a prominent role in shaping relations of work in South Africa. The study begins with a historical overview of trade unionism in South Africa. It then attempts to establish how trade unions have made use of the institution of collective bargaining, the importance of organisational rights to the trade union movement, the effectiveness of industrial action, and the emerging challenges threatening the vibrancy of trade unions. The overall aim is to assess whether the trade union movement is still a force to be reckoned with and its future role in influencing employment relations in South Africa.
Keywords: Labor unions -- South Africa; Apartheid -- South Africa; Industrial relations -- South Africa; Labor unions -- Law and legislation -- South Africa; Labor -- South Africa